BENTIK MAKROINVERTEBRATA SEBAGAI BIOINDIKATOR POLUSI LAHAN PERAIRAN - Tjokrokusumo, Sabaruddin Wagiman (Jurnal Hidrosfir Indonesia, 2006)
Inline with increasing population growth and progressive development inIndonesia, implementation of environmental regulation and enforcement ofenvironmental law, aquatic ecosystem was impacted by wastewater pollutionfrom several sources, including point and non-point sources of pollution.Aquatic pollution could be seen physically and can be traced through chemical and biological monitoring. Biologically water pollution can be detected through occurrence of flora and fauna of stream dwelling organisms because they were interacted physically and adapted with daily pollution materials and wastewater loadings. Stream dwelling flora and fauna either benthic macro and micro organisms have ability to adapt and assimilate pollution based on their sensitivities. Therefore their variable sensitivities can be used for approaching water pollution index. Hynes (1977) stated that water flora and fauna can be used as indicators of water pollution, such as algae, bacteria, protozoa, macroinvertebrates, and fish. However, a group of macro-invertebrates has been used for biomonitoring for decades, because of their habitat preferential factors, their slow mobility, biodiversity, and sensitivity. In addition, macroinvertebrates can been seen with naked eyes or using only with simple devices. A macroinvertebrate is an organism without backbone dwelling water ecosystem as its niche and habitat. This animal is ubiquitous in freshwater habitat, and also in brackish water and even in marine environment. An effort to use this biota as indicator of water pollution has been attempted in foreign countries such as Europe, America and Australia, and even South Africa. We believe that this kind of method can be applied one day in Indonesia.